0673 Effects Of Solriamfetol On Driving Performance In Participants With Excessive Daytime Sleepiness Associated With Obstructive Sleep Apnea. (27th May 2020) - Vinckenbosch, F; Asin, J; De Vries, N; Vonk, P; Donjacour, C; Lammers, G; Overeem, S; Janssen, H; Wang, G; Chen, D; Carter, L; Zhou, K; et al.
Abstract: Introduction: Excessive daytime sleepiness (EDS) in patients with obstructive sleep apnea (OSA) is associated with an increased risk of driving accidents. Solriamfetol, a dopamine/norepinephrine reuptake inhibitor, is approved in the US (Sunosi ® ) for EDS associated with OSA (37.5-150 mg/day). This study evaluated solriamfetol's effects on on-road driving performance in participants with EDS associated with OSA. Methods: In each period of this randomized, double-blind, placebo-controlled, crossover study (NCT 02806895; EudraCT 2015-003930-28), driving performance during an on-road driving test was assessed at 2 hours and 6 hours postdose following 7 days of treatment with solriamfetol (150mg/day × 3, then 300mg/day × 4) or placebo. The primary endpoint—standard deviation of lateral position (SDLP), a measure of "weaving, " at 2 hours postdose—was compared between solriamfetol and placebo per time point using a repeated mixed-effects analysis of variance model. Results: The study included 34 participants. Baseline characteristics reflected the broader OSA population (88% male; mean age=52 years; mean Epworth Sleepiness Scale score=14.4). SDLP at 2 hours postdose was statistically significantly lower following solriamfetol (least squares [LS] mean [standard error; SE], 18.83cm [0.63]) compared with placebo (19.92cm [0.63]): LS mean difference, -1.08cm; 95% confidence interval (CI), -1.85, -0.32; P =0.0062 (incomplete driving tests: solriamfetol, n=1; placebo, n=4), indicating better performance with solriamfetol. At 6 hours postdose, SDLP following solriamfetol (LS mean[SE], 19.24cm [0.63]) was statistically significantly lower compared with placebo (20.04cm [0.63]): LS mean difference, -0.80cm; 95% CI, -1.58, -0.03; P =0.0432 (incomplete driving tests: solriamfetol, n=3; placebo, n=7). Common adverse events (≥5%) with solriamfetol were headache, nausea, insomnia, dizziness, and agitation. Conclusion: Solriamfetol (300mg/day) improved SDLP, an important measure of driving performance, at 2 and 6 hours in participants with EDS associated with OSA. Support: Jazz Pharmaceuticals